J.W.A. Nicholson and Nathaniel Dowse Nicholson commissions and obituary - Nicholson, J. W. A. (James William Augustus), 1821-1887.; Nicholson, Nathaniel Dowse, 1790-1811.
Naval commission for Nathaniel Dowse Nicholson signed by Thomas Jefferson, 1808 January 1; Civil War naval commission for J.W.A. Nicholson signed by Abraham Lincoln, 1863 February 21; and obituary of J.W.A. Nicholson, New York Daily Graphic, 1887 November 1.
Naval officers.
Collection material in English.
Keywords: Jefferson, Thomas, -- 1743-1826.; Lincoln, Abraham, -- 1809-1865.; United States. -- Navy; Naval officers